The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1136/bmjopen-2013-004558
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three tests for faecal calprotectin in children and young adults: a retrospective monocentric study

Abstract: ObjectiveFaecal calprotectin is used as a sensitive marker for gastrointestinal mucosal inflammation. We compared the performance of three different assays in a large cohort of symptomatic paediatric patients.DesignRetrospective monocentric study.SettingInpatients and outpatients of a tertiary referral centre for paediatric gastroenterology.Participants304 symptomatic patients (163 males, aged 2–20 years) with active inflammatory bowel disease (IBD/A, n=130), IBD in clinical remission (IBD/R, n=62), other inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
1
18
1
4
Order By: Relevance
“…Recently, fecal calprotectin (FC) has been used as a biomarker for gastrointestinal mucosal inflammation; Prell et al . reported that normal FC concentration indicates absence of IBD in children and young adults . Hoekman et al .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, fecal calprotectin (FC) has been used as a biomarker for gastrointestinal mucosal inflammation; Prell et al . reported that normal FC concentration indicates absence of IBD in children and young adults . Hoekman et al .…”
Section: Discussionmentioning
confidence: 98%
“…Recently, fecal calprotectin (FC) has been used as a biomarker for gastrointestinal mucosal inflammation; Prell et al reported that normal FC concentration indicates absence of IBD in children and young adults. 14 Hoekman et al reported that in children with previously diagnosed IBD, clinical disease activity was only weakly associated with inflammatory markers such as FC and CRP. 15 Neither FC nor blood test results such as CRP or ESR are sufficient in themselves for diagnosis of pediatric IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Hay disponibles pocos estudios en la literatura que realicen comparaciones entre los distintos tipos de test de medición; todos ellos demuestran una gran sensibilidad de los test para la detección de inflamación mucosa, pero se observa una diferencia significativa en la especificidad y su valor absoluto, demostrando variabilidad entre cada tipo de test (27)(28)(29). En la pacientes, encontrando que con un punto de corte de 50 mcg/g, la sensibilidad y especificidad para diferenciar la patología orgánica de la funcional fueron 83% y 84% respectivamente (9).…”
Section: 4unclassified
“…Los estudios sobre las diferencias entre los distintos kits que existen en el mercado para la medida de CF, son muy escasos (27)(28)(29)107). En todos ellos se objetivan importantes diferencias entre los diferentes kits.…”
Section: 31unclassified
See 1 more Smart Citation